1962
DOI: 10.1136/sti.38.4.230
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Carcinoma of the Uterine Cervix in a V.D. Clinic

Abstract: Early diagnosis of carcinoma of the cervix by cervical smear has been the subject of many papers since the method was first described by Papanicolaou and Traut (1941) At a routine local genital examination, a scraping of cervical mucosa was taken with a wooden "mutton bone" spatula (Ayre, 1947) and spread evenly on to a slide marked with the patient's number. The slides were immediately stored in jars containing Schauddin's medium as a fixative and were taken to the laboratory once daily, where they were stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1964
1964
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…24 Unfortunately few reports of cytology screening in STD clinics have been published, and we are only aware of six previous reports, five of which were published in the 1950s and 1960s. [25][26][27][28][29] The two most recent reports came from Birmingham, England, in 333 196725 and Seattle, United States, in 198030 and gave incidences of dysplasia and carcinoma in situ of 69 9% and 11 4%o respectively. These figures were both well over five times the incidence of abnormal cytology reported by their countries' national screening programmes.…”
Section: Discussionmentioning
confidence: 99%
“…24 Unfortunately few reports of cytology screening in STD clinics have been published, and we are only aware of six previous reports, five of which were published in the 1950s and 1960s. [25][26][27][28][29] The two most recent reports came from Birmingham, England, in 333 196725 and Seattle, United States, in 198030 and gave incidences of dysplasia and carcinoma in situ of 69 9% and 11 4%o respectively. These figures were both well over five times the incidence of abnormal cytology reported by their countries' national screening programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Screening of special population groups for cancer of the cervix and uterus is probably more common than a review of the literature would indicate. Farrer and Tatham (5), reporting on a limited number screened in a venereal dis¬ ease clinic in St. Thomas Hospital, London, concluded that such screening ought to be en¬ couraged and adopted as routine procedure. Ferguson (6) pointed out in 1961 the signifi¬ cant yield of cancer in screening girls less than 19 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…early onset of coitus and multiple sex partners. So, carcinoma cervix can be considered as one of 3 rd generation STDs [7]. Majority of women were ignorant regarding causes treatment and prevention of STIs [8].…”
Section: Discussionmentioning
confidence: 99%